Whether waqf and endowment can ride the same legal vehicle in Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Ali, Zuraidah (2021)
Waqf and endowment concepts are used for fund-raising and charity in Malaysia. Nevertheless, both are under a separate legal framework. This study explores whether Waqf and Endowment can co-exist in one legal vehicle. It further investigates the various legal vehicles available under Malaysian law that can support the two concepts. It will then look into the legal possibility of implementing both waqf and endowment within one legal vehicle and the challenges arising.